2005
DOI: 10.1128/jb.187.13.4346-4352.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acetobacter aceti Possesses a Proton Motive Force-Dependent Efflux System for Acetic Acid

Abstract: Acetic acid bacteria are obligate aerobes able to oxidize ethanol, sugar alcohols, and sugars into their corresponding acids. Among them, Acetobacter and Gluconacetobacter species have very high ethanol oxidation capacity, leading to accumulation of vast amounts of acetic acid outside the cell. Since these bacteria are able to grow in media with high concentrations of acetic acid, they must possess a specific mechanism such as an efflux pump by which they can resist the toxic effects of acetic acid. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…Very recently, Matsushita et al (24) reported the presence of the efflux pump for acetic acid in the other strain of A. aceti. They concluded that the efflux pump is proton motive force dependent because transporter activity was dependent on pH, not on ATP, and was sensitive to a proton uncoupler.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Matsushita et al (24) reported the presence of the efflux pump for acetic acid in the other strain of A. aceti. They concluded that the efflux pump is proton motive force dependent because transporter activity was dependent on pH, not on ATP, and was sensitive to a proton uncoupler.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is likely that there is some other machinery conferring acetic acid resistance that is located in the cell membrane, because part of acetic acid toxicity is caused by serving as an uncoupling agent, which disturbs the proton motive force (2,7,9,36). Recently, the presence of a proton motive efflux system for acetic acid in A. aceti cultured on the glycerol medium has been reported (24); however, it seems unclear if it contributes to acetic acid resistance in acetic acid fermentation.…”
mentioning
confidence: 99%
“…All experiments were performed at least in triplicate, using protein concentrations of 50 (RSOV), 200 (ISOV), and ϳ700 g/ml (whole cells, corresponding to an OD 420 of 10) as determined by protein assay using a modified Lowry procedure (27) (13). Fluorescence Measurements of Membrane Potential (⌬) in RSOV and ISOV-Fluorescent probes, 3,3Ј-dipropylthiadicarbocyanine iodide (1 M) and bis-(1,3-dibutylbarbituric acid) pentamethine oxonol (1 M), were used to monitor ⌬ changes in energized vesicles as described (30). Fluorescence excitation and emission wavelengths were, respectively, 622 and 670 nm for 3,3Ј-dipropylthiadicarbocyanine iodide, and 588 and 614 nm for bis-(1,3-dibutylbarbituric acid)pentamethine oxonol.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular mechanisms of acetic acid resistance in Acetobacter aceti include adaptation of the cytoplasmic components (9,14) to internal acidification (32), acetic acid efflux via the AatA acetic acid:proton antiporter (31,39), and production of acid-inducible proteins identified by proteomic screens, many with undefined biochemical roles (28,52).…”
mentioning
confidence: 99%